Stakeholder Management Capability and Performance in Brazilian Cooperatives - Pavão, Yeda Maria Pereira; Rossetto, Carlos Ricardo (Review of Business Management, 2015)
Objective – The aim of this paper is to relate Stakeholder Management Capability (SMC) to economic-financial and social-environmental performance. Design/methodology/approach – Data collection occurred in 26 states and the Federal District of Brazil. There was validation of 171 questionnaires answered at the strategic and tactical levels in the context of cooperatives in 13 sectors of Brazil’s economy. Structural equation modeling was used as an application to verify the data with the use of exploratory and confirmatory factor analysis. Findings – The results made it possible to verify the relationship between SMC and the social and environmental performance. The coefficient found for the relationship between SMC and economicfinancial performance also had a positive effect. Practical implications – The research results provide evidence that SMC is directly related to the economic-financial and socialenvironmental performance of cooperative organizations. SMC may also contribute to the analytical process of organizations from the statistical dimension and an applied empirical structure. Originality/value – The model reached support in both relationships with significant values, demonstrating that the dimensions and scales used to measure it were satisfactory, validating the proposed model. This finding demonstrates that these organizations have the skills to meet the requirements of and manage stakeholders, even if one person plays different roles, i.e. the cooperative member, which is basically the owner, supplier, consumer and customer.